Marvel, machine or malnourished: exploring the sociology of the body in women`s artistic gymnastics - Frogley, M.; Oliver, E.; Palmer, C. (Journal of Qualitative Research in Sports Studies, 2019)
Women`s Artistic Gymnastics (WAG) requires its participants to perform acrobatic feats of aesthetic actions across four disciplines of apparatus: balance beam, asymmetric bars, vault, and the floor exercise. From the promotion of demure grace in the 1950s, to the acrobatic, youthful slimness of the 1970s and now the 21st century battle of muscular versus petite, WAG has seen many changes regarding representations of the successful female athletic body and associated coaching style and evaluation foci. The aim of this research was to explore the characteristics and practices of the modern gymnastics subculture, its apparent obsession with perfection and the place of the body within it. 7 ex-gymnasts were interviewed, who were female, between 16-25 years old, and had competed at club level or higher in WAG for a registered British Gymnastics Club. 7 key themes emerged during analysis: body culture, disordered eating, gymnastics culture and practice, the pressures of elite, searching for perfection, social network and tough love. It was discovered that most participants had a positive body image, however the influence of coaches, peers and judges on the gymnasts` perception of their bodies was evident. Practices such as weighing, competition pressure, team control and performing in pain, arose as potentially damaging to the body and one`s attitude towards it. Results indicate a need for a more grounded qualitative research to inform coach education in British Gymnastics, and the NHS, about the prevalence of eating disorders in elite / high performance (young) gymnasts and to understand the pressures in gymnastics subculture.